Oxygen Glucose Deprivation in Rat Hippocampal Slice Cultures Results in Alterations in Carnitine Homeostasis and Mitochondrial Dysfunction - Rau, Thomas F. (Public Library of Science, 2012)
Mitochondrial dysfunction characterized by depolarization of mitochondrial membranes and the initiation of mitochondrial-mediated apoptosis are pathological responses to hypoxia-ischemia (HI) in the neonatal brain. Carnitine metabolism directly supports mitochondrial metabolism by shuttling long chain fatty acids across the inner mitochondrial membrane for beta-oxidation. Our previous studies have shown that HI disrupts carnitine homeostasis in neonatal rats and that L-carnitine can be neuroprotective. Thus, this study was undertaken to elucidate the molecular mechanisms by which HI alters carnitine metabolism and to begin to elucidate the mechanism underlying the neuroprotective effect of L-carnitine (LCAR) supplementation. Utilizing neonatal rat hippocampal slice cultures we found that oxygen glucose deprivation (OGD) decreased the levels of free carnitines (FC) and increased the acylcarnitine (AC): FC ratio. These changes in carnitine homeostasis correlated with decreases in the protein levels of carnitine palmitoyl transferase (CPT) 1 and 2. LCAR supplementation prevented the decrease in CPT1 and CPT2, enhanced both FC and the AC∶FC ratio and increased slice culture metabolic viability, the mitochondrial membrane potential prior to OGD and prevented the subsequent loss of neurons during later stages of reperfusion through a reduction in apoptotic cell death. Finally, we found that LCAR supplementation preserved the structural integrity and synaptic transmission within the hippocampus after OGD. Thus, we conclude that LCAR supplementation preserves the key enzymes responsible for maintaining carnitine homeostasis and preserves both cell viability and synaptic transmission after OGD.